Multiculturalism and American Democracy - Zinman, M. Richard; Weinberger, Jerry, 1944-; Melzer, Arthur M. (Book collections on Project MUSE., 1998)
Choice Outstanding TitleMulticulturalism: is it the face of twentyfirst century America or merely a passing intellectual fad? With its celebration of ethnic diversity and strong advocacy of tolerance, this contemporary movement provides philosophical justification for many who seek to correct social inequities. But while its proponents see it as a means of promoting selfesteem among marginalized groups, its critics see it as a dangerous form of relativism that culminates, paradoxically, in a new form of intolerance.The fourteen essays in this volume address the pros and cons of multiculturalism and explore its relationship with liberal democracy. A team of stellar contributors--C. Vann Woodward, Linda Chavez, Stanley Fish, and others--offers viewpoints on multiculturalism from the perspectives of political theory, history, philosophy, and fiction.The editors first help explain multiculturalism by contrasting it with the Sixties counterculture. How is it, they ask, that yesterday's radicals, so concerned with economic justice, have given way to the multiculturalist preoccupation with identity politics? The contributors then explore different facets of the multiculturalism issue: they present disparate views of the stakes involved as older notions of pluralism and assimilation give way to multiculturalism; examine it in its relation to the principles of liberal democracy; and assess its place in public education. In a final section, the role of the arts in the multiculturalism debate is addressed by celebrated novelists J. M. Coetzee and Mario Vargas Llosa.Because multiculturalism is a movement without a leader or guiding document, its tenets remain difficult to define. This book not only tells what the controversy is about but also clarifies the concerns it should raise for thoughtful citizens. The points of view expressed here will prove helpful to those who are trying to frame their own opinions about multiculturalism--and they are guaranteed to spark new debate among those who have already chosen sides.